2013
DOI: 10.1007/s13277-013-0963-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer activity of DHA on gastric cancer—an in vitro and in vivo study

Abstract: Treatment of gastric cancer remains a major challenge, and new anticancer drugs are urgently required. This study investigated whether dihydroartemisinin (DHA), a semi-synthetic derivative of artemisinin, could inhibit the growth of gastric cancer both in vitro and in vivo. A series of in vitro experiments including MTT, colony-forming, wound healing, invasion, cell cycle, cellular senescence, and apoptosis assays were performed to examine the antiproliferative and antimetastatic effects of DHA on three gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…5e), corroborating the dominant role of Bak in DHA-induced intrinsic apoptosis in HCC cells [27]. In contrast, the Bax-mediated intrinsic pathway has been reported to play a key role in DHAinduced apoptosis in various cell lines [13,[18][19][20][21][22][23][24]. Therefore, the pro-apoptotic action of DHA is cell typedependent.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…5e), corroborating the dominant role of Bak in DHA-induced intrinsic apoptosis in HCC cells [27]. In contrast, the Bax-mediated intrinsic pathway has been reported to play a key role in DHAinduced apoptosis in various cell lines [13,[18][19][20][21][22][23][24]. Therefore, the pro-apoptotic action of DHA is cell typedependent.…”
Section: Discussionmentioning
confidence: 54%
“…Although reactive oxygen species (ROS) generated from the endoperoxide bridge contained in DHA contributes to the potent cytotoxic effects of DHA on cancer cells, DHA triggers different apoptotic pathways to mediate cell apoptosis [17]. Accumulated proofs have shown the important role of the Bax-dependent intrinsic apoptosis pathway in DHA-induced apoptosis of multiple types of cancer cells [15,[18][19][20][21][22]. Our recent studies also demonstrated that the Bax-mediated intrinsic apoptosis pathway played a dominant role in DHA-induced apoptosis of lung cancer cells [20,23,24], while the Bak-mediated intrinsic apoptosis pathway controlled the pro-apoptotic actions of the combined treatment with DHA and gemcitabine in inducing apoptosis of A549 cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis induced by DHA in different cancer cells has been reported [21][22][23][24][25][26][27][28][29][30]. In the present study, we examined apoptosis in human androgen-independent PC3 prostate cancer cells after DHA treatment, by flow cytometry and TEM.…”
Section: Discussionmentioning
confidence: 83%
“…Dihydroartemisinin (DHA), a semisynthetic derivative of artemisinin isolated from the Chinese medicinal plant Artemisia annua L., has been widely used as an effective antimalarial drug [15][16][17][18][19]. Recently, many studies have shown that DHA is the most potent anticancer agent among artemisinin and its derivatives [20], and has in vitro and in vivo anticancer activity in different types of human cancer cells, such as hepatocellular carcinoma, prostate cancer, gastric cancer, osteosarcoma, breast cancer, esophageal cancer, pancreatic cancer, lung cancer, and ovarian cancer [21][22][23][24][25][26][27][28][29][30][31]. It has been demonstrated that DHA can induce apoptosis and/or inhibit proliferation of cancer cells [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al (24) reported that miR-15b deactivated the MEK-ERK pathway through MMP-3 in 9L glioma cells. Sun et al (25) suggested that treatment of gastric cancer cells increased miR-15b expression corresponding with downregulation of MMP-9 and MMP-2.…”
Section: Discussionmentioning
confidence: 99%